Circular Vibration Planing of Inconel 718 - Nandita Kalyanakumara HETTIARACHCHI; Toshimichi MORIWAKI; Toshiro SHIBASAKA; Keiichi NAKAMOTO (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2008)
Circular vibration milling (CVM) is achieved by vibrating a milling cutter about the machine tool spindle axis in a circular path, in addition to its rotary motion. CVM has been proven capable of producing better surface finishes on difficult to cut materials. However, the CVM process is far slower than conventional milling process. In circular vibration planing (CVP) process, the cutting tool is clamped without rotation and fed at a speed comparable to the feed speed of conventional milling. By superimposing circular vibration motion, necessary cutting speed could be achieved keeping the feed speed at realistic values. Inconel 718 was machined by CVP and conventional milling at a similar feed rate. It was observed that CVP could reduce tool wear and hence produce better surface finishes than conventional milling. A geometric simulation showed a major difference between uncut chip shapes of the two processes. The difference of uncut chip shapes suggests that in CVP process, less rubbing occurs between tool flank face and work before the tool penetrates in to the work to form a chip. The reduced rubbing of the flank face is proposed as the reson for reduced tool wear in CVP when compared with conventional milling.